The Biography of a Writer as an Argument in (De)Canonisation - Satkauskytė, Dalia (Colloquia, 2024)
Despite the conception of the author’s death that was prevalent in the second half of the 20th century, the author’s biography always intervenes indirectly in the canonisation process, either a priori, as an additional argument for canonisation (e.g. participation in the national movement), or a posteriori, when the canonised author acquires, according to Yuri Lotman, the right to a biography. Moreover, biography becomes a significant factor in cases of revising and rewriting the canon, especially when it is related to political changes in society, e.g. in forming a Socialist Realist canon or the case of its radical deconstruction. The focus on biographical texts and authors’ biographies increases significantly in the 21st century, when literature itself tries to erase boundaries between fictional and biographical, and literary scholars discuss whether it is possible to separate the author from his or her work in the contexts of the historical memory and cancel culture. In this theoretical and historical framework, I discuss the role of the biography in the canonisation and decanonisation of a writer, and consider how these processes and the shift in the cultural paradigm influence interpretations of writers’ biographies.